Reconsidering Overlap-Based Measures for Quantitative Synthesis of Single-Subject Data: What They Tell Us and What They Don't. (May 2013) - Carter, Mark
Overlap-based measures are increasingly applied in the synthesis of single-subject research. This article considers two criticisms of overlap-based metrics, specifically that they do not measure magnitude of effect and do not adequately correspond with visual analysis. It is argued that these criticisms are based on fundamental misconceptions regarding the nature of effect sizes and their appropriate interpretation in single-subject research. Suggestions for considerations in evaluating single-subject research studies are offered, including the need to separately consider experimental control and magnitude of effect.